2020
DOI: 10.1029/2019jd031731
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multiscale Orography on the Initiation and Maintenance of a Precipitating Convective System in North China: A Case Study

Abstract: Using convection‐resolving Weather Research and Forecasting simulation, this work studies a heavy rainfall event that occurred in the Shanxi Plateau, North China on 21–22 May 2017. Of particular interest is the influence of multiscale orography on the initiation and maintenance of the precipitating convective system. Results showed that the initial convection was triggered over the small‐scale Taiyue Mountain in the Shanxi Plateau. In the nighttime, with a stable boundary layer, orographic gravity waves were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Several field campaigns were carried out worldwide to understand DCSI and evolutionary processes over complex terrain areas to (a) improve prediction of the location and timing of new convection and (b) improve quantitative precipitation forecasting (QPF) skills [23,[30][31][32][33][34]. Much work has been done to study the physical mechanisms of DCSI based on numerical weather models, and/or multi-platform measurements over the North China, South China and Eastern China, respectively [35][36][37][38]. Several statistical studies of DCSI have also been done in these regions in recent years using satellite and/or Doppler weather radar measurements [19,26,27,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Several field campaigns were carried out worldwide to understand DCSI and evolutionary processes over complex terrain areas to (a) improve prediction of the location and timing of new convection and (b) improve quantitative precipitation forecasting (QPF) skills [23,[30][31][32][33][34]. Much work has been done to study the physical mechanisms of DCSI based on numerical weather models, and/or multi-platform measurements over the North China, South China and Eastern China, respectively [35][36][37][38]. Several statistical studies of DCSI have also been done in these regions in recent years using satellite and/or Doppler weather radar measurements [19,26,27,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Effective representation of complex terrain and related effects has long been a difficult problem in numerical simulation studies (Davies & Brown, 2001; Jiménez & Dudhia, 2012; Phillips, 1957; Wallace et al., 1983; Xu et al., 2019). Adopting high‐resolution grid‐scale topography improves the model performance (Hua et al., 2020; Ji & Kang, 2013). However, the models perform worse when increasing the resolution to a certain degree without correspondingly improving the description of physical process (Carvalho et al., 2012; Falasca & Curci, 2018; Mass et al., 2002; Maurya et al., 2018), especially the sub‐grid terrain related processes (Elvidge et al., 2019; Lalande et al., 2021; Yu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the afternoon, the ascending branch of the MPS is located near the mountains and promotes the precipitation in the mountain areas, while in the evening, the ascending branch is located in plains or basins and facilitates the precipitation in plains or basins [ 4 , 23 , 24 ]. The topography of North China is complex, and the topographic forcing is closely related to the heavy rainfall in North China [ 10 , 25 ]. Past studies have shown that lifting of warm and wet low-level flow forced by mountains is beneficial to the heavy precipitation on the eastern slope of mountains near the plain [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%